Foreign students in higher education institutions in Portugal, expectations and reality: A case study - Mauritti, R.; Pintassilgo, S.; Belchior-Rocha, H.; Mendes, J.; Ramos, D. (EDULEARN22 Proceedings, 2022)
The objective of this presentation is to provide a case study analysis of the presence of foreign students in higher education institutions in Portugal, in a public university, focusing on students from African Portuguese Speaking Countries (PALOP), namely, scholarship students entering the Portuguese higher education system, through the protocol between the Ministry of Science and Higher Education, the Ministry of Internal Administration, the Ministry of Foreign Affairs and the governments of the PALOP. The analysis considers two dimensions. On the one hand, it considers the volume and evolution of the presence of this set of students in the Portuguese higher education system, in the light of the institutional and legislative framework, which enables international mobility and favors the entry of students from these nationalities into higher education in Portugal, and influences the dynamics of their progression. On the other hand, the real conditions under which those students enter higher education in Portugal are analyzed, as well as the possible dissonance between the expectations built on the basis of a normative discourse, established and legislated, and the experiences actually lived in the context of their reception, and the difficulties experienced by those who enter with "scholarship status" on the basis of a term of responsibility that exempts the host state from any social responsibility. The differences between the educational systems have particular relevance in the adaptation of these students, from the language, which, being Portuguese, is one of the greatest difficulties in interpreting texts and consulting bibliographies, digital literacy, and social and economic needs that make access to elementary resources (photocopying, personal computer, Internet, and daily mobility) difficult.